FUNGAL INFECTION OF STORED ARABICA COFFEE (Coffea arabica) BEANS IN SOUTH SULAWESI PROVINCE, INDONESIA - Okky Setyawati Dharmaputra; Santi Ambarwati; Ina Retnowati; Nijma Nurfadila (SEAMEO BIOTROP, 2019)
Indonesia is the world's fourth-largest coffee producer after Brazil, Vietnam, and Colombia, in which one of its well-known coffee originates from the Toraja region, South Sulawesi. As such, Indonesia has to compete with these countries in producing good quality coffee beans. Consequently, this research aimed (a) to obtain information on the postharvest handling methods of Arabica coffee (C. arabica) beans in Tana Toraja Regency, North Toraja Regency, and Makassar Municipality, Indonesia, and (b) to investigate the occurrence of fungi (including ochratoxin A producing fungi) in stored Arabica coffee beans collected from various stages of the delivery chain. The data collection process included surveys, interviews, and sample collections conducted in May and July 2016 at each level of the delivery chain. The moisture content (MC) and the physical quality of the beans were also measured to determine its quality. Sixty-four (64) coffee bean samples were collected, consisting of 27 samples from the farmers, 15 samples from the collectors, 13 samples from the traders, and 9 samples from the exporters. The results showed that the moisture contents of coffee beans collected from the farmers and bean collectors (42.5%) were significantly higher than the maximum tolerable limit determined by the Indonesian National Standard (SNI) (13%), while the MC of the beans from the traders and exporters (9.7–10.9%) was significantly lower. Based on the total defective values, coffee beans from the farmers had more diverse grades (1–6) than those at other levels. Penicillium citrinum was the dominant fungus found in those beans collected from the farmers, collectors, and traders, while Aspergillus niger was the dominant fungus found in those beans from the exporters. At trader level, 46% of the samples were infected by Aspergillus ochraceus and A. niger, which are known as ochratoxin A (OTA) producing fungi. At exporter level, 44% of the samples were infected by A. ochraceus, while 78% of the samples were infected by A. niger. Thus, the postharvest handling methods conducted especially by farmers and collectors of Arabica coffee beans should be improved to reduce the moisture content and to increase the grade quality of the coffee beans.